Professionally Applied Topical Fluoride and Restorative - Stephen A. Eklund, DDS, MHSA, DrPH; James L. Pittman, DDS, MS; Keith E. Heller, DDS, MPH, DrPH (Blackwell Synergy, 2000)
This study evaluates the association between use of professionally applied topical fluoride and use of interproximal restorations in primary and permanent teeth of children